2017
DOI: 10.1002/jor.23464
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of magnetic field interactions and radiofrequency-radiation-induced heating of metallic spinal implants in 7 T field

Abstract: The safety of metallic spinal implants in magnetic resonance imaging (MRI) performed using ultrahigh fields has not been established. Hence, we examined whether the displacement forces caused by a static magnetic field and the heating induced by radiofrequency radiation are substantial for spinal implants in a 7 T field. We investigated spinal rods of various lengths and materials, a screw, and a cross‐linking bridge in accordance with the American Society for Testing and Materials guidelines. The displacement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…Despite the considerable construct length and the large amount of metal, the maximum RF-induced temperature increase of the spinal implants in the worst case conditions (SAR 2 W/kg, 15 min MR acquisition) was only 1.3 K. The RF-induced heating was even less when two cross-links were used, although electrically closed loops (coils) can favor heating of the surroundings [19]. These results are in agreement with the findings of Tsukimura et al [1] for a 200-mm implant at 7 T. A review [20] demonstrated that low heating (up to 43°C) for several hours causes no damage and that heating to 44°C for 200 min leads only to transient erythema. Therefore, it can be assumed that adverse biological effects due to RF-induced heating of the investigated pedicle-screwrod system in scoliosis patients, examined with a 1.5 to 3 T MRI in a supine position, become unlikely.…”
Section: Astm F2182: Rf-induced Heatingsupporting
confidence: 90%
See 3 more Smart Citations
“…Despite the considerable construct length and the large amount of metal, the maximum RF-induced temperature increase of the spinal implants in the worst case conditions (SAR 2 W/kg, 15 min MR acquisition) was only 1.3 K. The RF-induced heating was even less when two cross-links were used, although electrically closed loops (coils) can favor heating of the surroundings [19]. These results are in agreement with the findings of Tsukimura et al [1] for a 200-mm implant at 7 T. A review [20] demonstrated that low heating (up to 43°C) for several hours causes no damage and that heating to 44°C for 200 min leads only to transient erythema. Therefore, it can be assumed that adverse biological effects due to RF-induced heating of the investigated pedicle-screwrod system in scoliosis patients, examined with a 1.5 to 3 T MRI in a supine position, become unlikely.…”
Section: Astm F2182: Rf-induced Heatingsupporting
confidence: 90%
“…When the patient is lying supine, the implant is located in the middle of the scanner and therefore has the lowest risk of heating. Tsukimura et al [1] did not find any significant difference between Ti rods with different alloys. Moreover, the Ti rods with CoCr alloy have the ability to produce higher correction rates in adolescent idiopathic scoliosis (AIS) and provide significant and stable spinal correction compared to Ti rods with TiCP alloy of the same diameter [27].…”
Section: Astm F2182: Rf-induced Heatingmentioning
confidence: 86%
See 2 more Smart Citations
“…In our previous study, we investigated whether the displacement forces caused by a static magnetic field and the heating induced by radiofrequency (RF) radiation are substantial for spinal implants in a 7‐T field and reported on its safety in accordance with the American Society for Testing and Materials (ASTM), which sets MRI compatibility standards…”
Section: Introductionmentioning
confidence: 99%